2017
DOI: 10.1002/2016gl072245
|View full text |Cite
|
Sign up to set email alerts
|

High permeability explains the vulnerability of the carbon store in drained tropical peatlands

Abstract: Tropical peatlands are an important global carbon (C) store but are threatened by drainage for palm oil and wood pulp production. The store's stability depends on the dynamics of the peatland water table, which in turn depend on peat permeability. We found that an example of the most abundant type of tropical peatland—ombrotrophic domes—has an unexpectedly high permeability similar to that of gravel. Using computer simulations of a natural peat dome (NPD) and a ditch‐drained peat dome (DPD) we explored how suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 29 publications
2
78
1
2
Order By: Relevance
“…5C). Very high permeability near the peat surface is consistent with our observations of more void space higher in the peat profile and also with recent data from other tropical peatlands (30 …”
Section: Resultssupporting
confidence: 92%
“…5C). Very high permeability near the peat surface is consistent with our observations of more void space higher in the peat profile and also with recent data from other tropical peatlands (30 …”
Section: Resultssupporting
confidence: 92%
“…Many other studies have shown how depth‐integrated decay of peat (usually the dominant component of R E ) increases as the water table deepens (see Baird et al., ). The combined P G and R E data from Hirano et al.…”
Section: Discussionmentioning
confidence: 98%
“…Hirano et al (2012) investigated the C balance of drained and near-natural ombrotrophic tropical peatlands using eddy correlation. For a near-natural site, they found that gross primary production (P G ) showed a quadratic relationship with water- Baird et al, 2017). The combined P G and R E data from Hirano et al (2012) show that net rates of peat accumulation are highest when a tropical peatland is at its wettest and lowest when it is at its driest.…”
Section: Allogenic and Autogenic Controls On Peatland Developmentmentioning
confidence: 99%
“…al., ; Ingram, ; Leifeld et al, ; Morris et. al., ], the development of pipes [ Cunliffe et al, ; Holden and Burt, ; Holden, , ], changes in column height due to mechanical compaction [ Baird et al, ; Hooijer et al, ; Williamson et al, ; Wösten et al, ], and the development of bare peat [ Tallis, ; Parry et al, ] (all are discussed in supporting information, Text S2). While these processes could be developed in a future version of the model, our aim at this stage was to simulate the development of plausible peatlands and to explore the effects of artificial drainage in space as well as time; which is different from previous studies that use 1‐D models [e.g., Frolking et al ., ; Kurnianto et al ., ].…”
Section: Methodsmentioning
confidence: 99%